EFFECT OF BREWING TEMPERATURE AND TIME ON VITAMIN C CONTENT AND ANTIOXIDANT ACTIVITY OF EDIBLE FLOWER INFUSES - Pulung Nugroho; Karina Bianca Lewerissa; Francies Seva Gentaarinda (Jurnal Pangan dan Agroindustri, 2023)
Dried chrysanthemum, jasmine and butterfly pea are raw materials for dip infused with antioxidant and vitamin C content. This study aimed to determine the effect of temperature and infusion time on vitamin C content and antioxidant activity. A two-factorial design was used with the first factor being the infusion temperature of 30, 50 and 70 °C. The second factor was infusion time of 1, 3 and 5 minute. Vitamin C content was determined by UV spectrophotometric method (Thermo Scientific Genesys 10 S UV), antioxidant activity by DPPH method, and moisture content by moisture analyzer. The optimum results of vitamin C content of dry samples at 30 °C brewing temperature for 3 minutes and 70 °C brewing temperature for 5 minutes was 0.29%. The vitamin C content of the wet flower control at 70 °C for 5 minutes was 0.53%. The optimum antioxidant activity of the dry sample at 50 °C brewing temperature for 3 minutes was 34.61% and that of the fresh flower control at 70 °C brewing temperature for 5 minutes was 94.14%. The moisture content of dried Chrysanthemum was 7.30%, dried Jasmine was 6.25% and dried butterfly pea was 7.24%.